Application of multi-stage ozonation / advance oxidation process (AOP) and biological treatment for colour, BOD and COD removal of azo dye industrial effluent - Che Zulzikrami, Azner Abidin; Fahmi, Muhamad Ridwan; Haidar, S. Al-Maroof; Nazerry Rosmady, Rahmat (Universiti Kebangsaan Malaysia (UKM), 2011)
Regional Engineering Postgraduate Conference 2009 (EPC 2009) organized by Faculty of Engineering & Built Environment, Universiti Kebangsaan Malaysia, from 20th - 21st October 2009 at Palm Garden Hotel, Putrajaya, Malaysia.